Genome Wide Analysis of Sex Difference in Gene Expression Profiles of Bone Formations Using sfx Mice and BXD RI Strains - Yue Huang; Xiaodong Zhu; Lishi Wang; Xiaoyun Liu; Lu Lu; Weikuan Gu; Yan Jiao (The Scientific World Journal)
The objective of this study is to identify sex differentially expressed genes in bone using a mouse model of spontaneous fracture, sfx, which lacks the gene for L-gulonolactone oxidase (Gulo), a key enzyme in the ascorbic acid (AA) synthesis pathway. We first identified the genes that are differentially expressed in the femur between female and male in sfx mice. We then analyzed the potential gene network among those differentially expressed genes with whole genome expression profiles generated using spleens of female and male mice of a total of 67 BXD (C57BL/6J X DBA/2J) recombinant inbred (RI) and other strains. Our result indicated that there was a sex difference in the whole genome profiles in sfx mice as measured by the proportion of up- and downregulated genes. Several genes in the pathway of bone development are differentially expressed between the male and female of sfx mice. Comparison of gene network of up- and downregulated bone relevant genes also suggests a sex difference.